THE ROLE OF INFORMATION TECHNOLOGY IN THE PHARMACEUTICAL INDUSTRY - Kuvatov Jurʼatbek Dilshadbekovich (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
In the fast-paced and dynamic landscape of the pharmaceutical industry, Information Technology (IT) has emerged as a crucial driving force, revolutionizing the way companies operate, innovate, and deliver healthcare solutions. This article explores the multifaceted role of information technology in the pharmaceutical sector, shedding light on its transformative impact on research and development, manufacturing, regulatory compliance, and patient care.